Organizational and institutional responses to climate change: Insights from Bangladesh, Ethiopia, Kenya, and Mali - Ragasa, Catherine; Sun, Yan; Bryan, Elizabeth; Abate, Caroline; Alemu, Atlaw; Keita, Mahamadou Namori (International Food Policy Research Institute, 2014)
This policy note summarizes research exploring the challenges and opportunities associated with building human, organizational, and institutional capacity to respond effectively to the adverse impacts of climate change as they relate to agriculture and rural livelihoods in developing countries. The findings offer insights into levels of awareness, practices, and organizational and institutional issues based on interviews with practitioners involved in climate change adaptation in government agencies, local and international organizations, and think tanks in Bangladesh, Ethiopia, Kenya, and Mali.